The Influence of Organizational Culture, Job Rotation, and Work Motivation on Employee Performance at the Lubuk Pakam Pratama Tax Services Office - Syah, Amirul; Nasution, Iqbal Halim Ramadhan; Yusri, Iswandi; Harahap, Nurhalijah; Simatupang, Paisal Amir; Supriadi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to determine the influence of organizational culture, job rotation, and work motivation simultaneously on employee performance at the Lubuk Pakam Pratama Tax Services Office. The research was conducted at the Lubuk Pakam Pratama Tax Services Office on Jalan P Diponegoro Number 30-A, Medan, with a population of 122 individuals and a research sample of 55 individuals. Data collection was carried out through interviews, questionnaires, and documentation. The data analysis method used was multiple regression analysis using the IBM SPSS Statistics software version 25. The findings of the analysis reveal that the performance of employees at the Lubuk Pakam Pratama Tax Services Office is positively influenced by organizational culture, as evidenced by the results of the t-table analysis (3.603 > 2.008) at n = 55 and a 95% significance level. Job rotation does not significantly affect the performance of Lubuk Pakam Pratama Tax Services Office employees, supported by the t-value < t-table analysis (0.444 < 2.008) at n = 55 at a 95% significance level. On the other hand, work motivation has a significant impact on the performance of employees at the Lubuk Pakam Pratama Tax Services Office, as supported by the t-value > t-table (3.613 > 2.008) at n = 55 with a 95% significance level. The calculated F-value > F-table (21.926 > 2.79) indicates that collectively, there is a positive and significant influence of organizational culture, job rotation, and work motivation on the performance of Lubuk Pakam Pratama Tax Services Office employees.